Application of a simple and rapid LC-MS/MS method for determination of danshensu in human plasma for an oral pharmacokinetic study of Danshen granules in Chinese healthy subjects - Fu, Shujun; Li, Lifeng; Qiu, Feng; Wang, Baohe; Du, Wuxun; Feng, Limin (Analytical methods, 2014)
A simple and rapid liquid chromatography-electrospray ionization-tandem mass spectrometry method is developed and validated for the determination of danshensu in plasma of Chinese healthy subjects after oral administration of Danshen granules. After liquid–liquid extraction with ethyl acetate, danshensu and chloroamphenicol (internal standard, IS) were separated on an Agilent Zorbax XDB-C 18 column using a gradient mobile phase consisting of water (0.1% formic acid)–acetonitrile (0.1% formic acid) at a flow rate of 0.45 mL min −1 . The detection was performed in multiple reaction monitoring mode, using the transitions of m / z 196.9 → 134.8 and m / z 320.9 → 151.9 for danshensu and chloroamphenicol, respectively. The method was linear over the range of 0.50–500 ng mL −1 using only 100 μL of plasma and the lower limit of quantification was 0.50 ng mL −1 . The intra-day and inter-day precisions (% RSD) were all less than 15% and the accuracies (% RE) were within the range of ±15%, and recoveries were between 85.0% and 115%. The validated method was successfully applied to an explorative pharmacokinetic study of danshensu in Chinese healthy subjects after oral administration of Danshen granules. After oral administration, T max and C max values of danshensu were found to be 0.83 ± 0.13 h and 257 ± 73.8 ng mL −1 , respectively. Plasma concentrations declined with t 1/2Z of 1.65 ± 0.35 h.